Have Capital Market Anomalies Worldwide Attenuated in the Recent Era of High Liquidity and Trading Activity? - Benjamin R. Auer; Horst Rottmann (Center for Economic Studies and ifo Institute (CESifo), 2018)
We revisit and extend the study by Chordia et al. (2014) which documents that, in recent years, increased liquidity has significantly decreased exploitable returns of capital market anomalies in the US. Using a novel international dataset of arbitrage portfolio returns for four well-known anomalies (size, value, momentum and beta) in 21 developed stock markets and more advanced statistical methodology (quantile regressions, Markov regime-switching models, panel estimation procedures), we arrive at two important findings. First, the US evidence in the above study is not fully robust. Second, while markets worldwide are characterised by positive trends in liquidity, there is no persuasive time-series and cross-sectional evidence for a negative link between anomalies in market returns and liquidity. Thus, this proxy of arbitrage activity does not appear to be a key factor in explaining the dynamics of anomalous returns.
Keywords: G14; G15; 330; capital market anomalies; attenuation; liquidity; quantile regression; Markov regime-switching; panel analysis